2017
DOI: 10.1051/0004-6361/201628796
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and density structure of a recurring active region jet

Abstract: We present a study of a recurring jet observed on October 31, 2011 by SDO/AIA, Hinode/XRT and Hinode/EIS. We discuss the physical parameters of the jet such as density, differential emission measure, peak temperature, velocity and filling factor obtained using imaging and spectroscopic observations. A differential emission measure (DEM) analysis was performed at the region of the jet-spire and the footpoint using EIS observations and also by combining AIA and XRT observations. The DEM curves were used to creat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 37 publications
8
29
1
Order By: Relevance
“…The EM analysis confirms that the hot plasma of temperature 5-8 MK was present at the footpoint region and also showed the presence of Fe xviii 93.93 Å emission, whereas the spire was at a low temperature of 2 MK. The spire temperature was found to be in good agreement with the temperatures obtained in other studies of AR jets (Mulay et al 2016(Mulay et al , 2017. The electron number densities in the spire and footpoint were found to be an order of magnitude lower compared to the densities measured for other jets studied by Mulay et al (2016Mulay et al ( , 2017Mulay et al ( , 2018.…”
Section: Summary and Discussionsupporting
confidence: 86%
“…The EM analysis confirms that the hot plasma of temperature 5-8 MK was present at the footpoint region and also showed the presence of Fe xviii 93.93 Å emission, whereas the spire was at a low temperature of 2 MK. The spire temperature was found to be in good agreement with the temperatures obtained in other studies of AR jets (Mulay et al 2016(Mulay et al , 2017. The electron number densities in the spire and footpoint were found to be an order of magnitude lower compared to the densities measured for other jets studied by Mulay et al (2016Mulay et al ( , 2017Mulay et al ( , 2018.…”
Section: Summary and Discussionsupporting
confidence: 86%
“…The nonthermal velocities obtained from the Fe xxiv show good agreement with those obtained by Doschek et al (2015) in their individual study of M-class flare which showed surge like plasma ejection. The electron number density values obtained in the footpoint region of jet 1 and 2 were found to be lower than the values obtained for the jet studied in Mulay, Del Zanna, and Mason (2017b) and Doschek et al (2015), but show good agreement with the values obtained for the jet studied in Mulay et al (2016). The superhot plasma of 27 (25) MK was confirmed by FERMI during the rise (peak) phase of jet 1 whereas; peak temperature of 29 MK was measured at jet 2.…”
Section: Discussion and Summarysupporting
confidence: 77%
“…The densities obtained in the footpoint region of jet 1 and 2 using Fe xiv density diagnostics were found to be lower than the values obtained by Mulay, Del Zanna, and Mason (2017b) and Chifor et al (2008) using Fe xii density diagnostics except for one slit position (slit 19 for Fe xiv for AR jet 2) where the densities show good agreement. The densities show good agreement with the values obtained by Mulay et al (2016) which were lower limits to the densities.…”
Section: Density Diagnostics Using the Fe XIV Line Ratiocontrasting
confidence: 64%
See 2 more Smart Citations